Mechanical and material heterogeneity, strain localization and deformation rate effects in crushable expanded polystyrene foams - Yao, Francis; Joshi, Meet; Bland-Rothgeb, Megan; Cripton, Peter; Cronin, Duane; Magliaro, John (Frontiers in Mechanical Engineering, 2025)
Low-density expanded polystyrene (EPS) foams are widely used in lightweight energy absorption systems such as helmets due to their ability to readily mold into complex geometries. However, varying material flow and cooling rates during manufacturing produce exterior skin layers with substantially higher density and aspect ratio from the core, and the resultant mechanical properties have not been quantified. Previous studies assumed EPS foams were homogeneous, overlooking or intentionally removing the skin from test specimens and constrain their scopes to out-of-plane compression. In this study, closed-cell EPS foam pucks of 30, 50, 80, and 100 g/L were tested under in-and out-of-plane compression at loading rates spanning 0.001–10/s. Specimens were prepared with as molded and core (skin removed) configurations to quantify anisotropy from heterogeneity. Measurements revealed a 98% ± 8% higher density in the skin layers relative to nominal material density and cells skewed 41% ± 6% in the in-plane direction. As-molded specimens exhibited a 38% ± 4% higher plateau stress for in-plane loading compared to out-of-plane, highlighting foam cell elongation as a key strengthening mechanism. Quasi-orthotropic behavior was observed for the core foam material, which possessed more evenly sized cells. Digital image correlation quantified rate-dependent strain localization, providing novel evidence of internal pressure redistribution from viscous gas dynamics within the EPS beads, with 39% lower peak true strains, on average, measured at 10/s compared to 0.001/s. Unloading data also revealed progressive increases in post-crushing strain recovery, increasing an order of magnitude from 0.04 mm/mm to 0.42 mm/mm between 0.001-10/s for the 30 g/L group, confirming more even load distribution and cell fracture mitigation at elevated rates.